Analysis of Metaphor in Harris Jung’s Songs - Atallah, Nadhira -; Wibowo, Hanafi (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
This study, titled "Analysis of Metaphors in Harris J's Songs," aims to investigate, classify, evaluate, and interpret the figurative language present in selected songs by Harris J. The primary focus is on identifying the use of metaphor and its broader implications in his lyrics. Figurative language, including metaphor, is a prominent feature in Harris J’s music, contributing to the depth and richness of his lyrical content. The study delves into how these literary devices function within the context of his songs, exploring the themes, emotions, and messages conveyed through such language. By analyzing the lyrics, the research uncovers the diverse connotations associated with each type of figurative expression, shedding light on how Harris J uses metaphors to create nuanced and evocative narratives. This research contributes to the field of literary and musical analysis by offering insights into the role of figurative language in modern spiritual and inspirational music.